Comparison of theoretical and analytical investigation on axial compressive behaviour of concrete filled steel tubular columns. (2021) - Venkat Raman, S.; Elango, K.S.; Remya, P.R.; Saravanakumar, R.; Rajeshkumar, V.; Vivek, D.
Abstract: Concrete filled steel tubular (CFST) members has its successive footprints in the construction industry, owing to its high load carrying capacity, improved ductile performance, large energy absorption capacity etc. CFST column has its own advantages like maximizing the useable floor area and minimizing the need of formwork. In this research work, experiments are carried out on 8 circular CFST columns with 60 mm diameter and 2.5 mm thickness. The parameters varied are height (960 mm, 900 mm, 840 mm and 750 mm) and the in-filled materials like normal strength concrete and high strength concrete. The study mainly focused on analysing the codal provisions like Eurocode4, ACI and AS codes with the experimental results. From the study, the influence of slenderness ratio over effect of confinement is observed and evaluated. As the codal provision seems to be too conservative in predicting the compressive behaviour of CFST columns, a modified approach is derived. The analytical expression predicted by this simplified method is applicable for CFST columns with L/D ratio varies from 13 to 16.